Comparison of Histological Architecture of Paraffin Embedded and Indigenously Plastinated Tissues - Manjunatha, K.; Prasad, R. V.; Jamuna, K. V.; D’souza, Placid E.; Rao, Suguna; Ramkrishna, V. (Indian Journal of Veterinary Anatomy, 2015)
The sections of spleen, liver and kidney of pig were studied histologically before and after indigenous plastination. The light microscopic observations of plastinated sections revealed an excellent maintenance of tissues morphology. The solvent induced shrinkage artifact was completely absent unlike that of paraffin sections. To conclude, the indigenously plastinated tissue sections can also be used for histological and histopathological studies, however, proper deplastination prior to histological procedures may improve the differential staining, clarity and sharpness of microscopic details.